Language in Cinema: A Pragmatic Study of Violation Contexts in Disney’s Animated Film Zootopia - Andries, Fivy A.; Walalangi, Darryl Grant; Posumah, Jennie; Iroth, Santje; Tulus, Arie; Lengkoan, Fergina (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2025)
Language in animated films serves not only as a medium for storytelling but also as a reflection of pragmatic norms that govern social interaction. Although politeness strategies have been widely studied in natural discourse, there remains a notable gap in understanding how violations of these norms are embedded within cinematic dialogues, especially in films intended for all age groups. This study investigates the violation of politeness maxims proposed by Geoffrey Leech, including the Tact, Generosity, Approbation, Modesty, Agreement, and Sympathy maxims, as portrayed in the interactions involving Judy Hopps, the main character in Disney's Zootopia. Utilizing a qualitative descriptive method, the research analyzes selected utterances from the movie transcript and audiovisual scenes, focusing on the types of maxims violated and the emotional responses elicited. The results indicate that all six maxims are violated by supporting characters, with the Approbation Maxim emerging as the most frequently violated, comprising 44.4 percent of cases. These violations often lead to emotional consequences for the main character such as frustration, disappointment, and a sense of exclusion. This study contributes to the field of pragmatics by highlighting how impoliteness is constructed and perceived in fictional dialogues, providing new insights into language use in media contexts. Furthermore, it emphasizes the potential of animated films as valuable resources for teaching pragmatic awareness and promoting respectful communication. By critically examining how politeness is portrayed and breached, the study calls attention to the broader implications of media discourse in shaping audience perceptions of social interaction and linguistic behavior.